Pengaruh Waktu Perendaman Di Dalam Perasaan Jeruk Lemon Terhadap Kadar Formalin Pada Ikan Asin Jambal Roti - Hery Prambudi; Usdiyanto; Rizal Ibrahim Aji; Endah Aisyah Ningrum (Lembaga Pengembangan Kinerja Dosen, 2024)
Salted jambal roti fish often contains high levels of formaldehyde for reasons of price and long shelf life. Formalin is a hazardous material for human health. Citric acid contained in lemon is believed to be able to reduce formaldehyde levels contained in salted fish. Salted fish contains a lot of formalin levels because of the low price and long shelf life. This study aims to determine the effect of the soaking time of lemon juice on formalin levels in salted jambal roti fish. The method used was pre-experiment with a one-group pretest-postest design. Samples of salted jambal roti fish were treated with lemon juice immersion with 100% concentration for 0, 30, 45, 60, 75, 90, and 120 minutes. Formalin levels were analyzed using a uv-vis spectrophotometer. The results showed that the immersion time of lemon juice affects the formalin content in salted jambal roti fish. The largest decrease in formalin levels occurred in soaking for 120 minutes with an average of 3,750 ppm.